Precipitation spatial patterns in cities with different urbanisation types: Case study of Novi Sad (Serbia) as a medium-sized city - Savić, Stevan; Kalfayan, Mathias; Dolinaj, Dragan (Geographica Pannonica, 2020)
A direct outcome of the global climate change is a modification of seasonal precipitation patterns, visible at monthly temporal scale. In central Europe, it includes higher frequency of high intensity rainfalls, occurring mostly during spring and summer. These heavy rainfalls induce pluvial floods in urban areas due to high percentage of impervious surface and limited drainage systems. This hazard affects Central European cities and impact many receptors including lives, infrastructures, private properties or again towns functioning. This study focused on monitoring precipitation events in order to reveal precipitation pattern across two different type of land cover: urban and suburban/rural areas of Novi Sad (Serbia). Measurements from seven rain gauge stations were used as input data, covering the period 2015-2018. The precipitation data were analysed through 12 precipitation indices, whose nine were defined by Expert Team on Climate Change Detection and Indices (ETCCDI) and three additional were created for this study. Based on their locations, the stations were defined as ‘urbanized’ or ‘non-urbanised’ group.The concept of Local Climate Zone (LCZ) was used to classify the urbanised areas LCZ1-8, the non-urbanised areas LCZ9 and the land cover zones (LCZ A-G). A statistical analysis based on the ANOVA F-test was conducted, defining significant threshold at 90 for α = 0.01 and at 95% for α = 0.05. The obtained results make appear 1 relation for the CDD index at 95% and 2 relations at 90% for CDD and Rp95 indices, showing a relation between heavy rainfall and type of land cover. Statistical results underline the need of denser station network and longer monitoring period to proceed to stronger statistical test and the possible establishment of other relation with the climate indices.
Keywords: urban climate; heavy rainfall; monitoring network; precipitation indices; pluvial flood; Novi Sad